Including measures of chronic kidney disease to improve cardiovascular risk prediction by SCORE2 and SCORE2-OP. (3rd October 2022) - Matsushita, K; Kaptoge, S; Hageman, S H J; Visseren, F L J; Pennells, L; Coresh, J
Abstract: Background: The 2021 ESC guideline on cardiovascular disease (CVD) prevention qualitatively categorizes moderate and severe chronic kidney disease (CKD) as high and very-high CVD risk status regardless of other factors like age and does not include estimated glomerular filtration rate (eGFR) and albuminuria in its algorithms, SCORE2 and SCORE2-OP, to predict CVD risk. Purpose: To develop and validate an "Add-on" to incorporate CKD measures into these algorithms, using a validated approach. Methods: In 3, 054, 840 participants from 34 datasets, we developed three Add-ons (eGFR only, eGFR + urinary albumin-to-creatinine ratio [ACR] [the primary Add-on], and eGFR + dipstick proteinuria) for SCORE2 and SCORE2-OP. We validated c-statistics and net reclassification improvement (NRI), accounting for competing risk of non-CVD death, in 5, 995, 067 participants from 33 different datasets. Results: In the target population of SCORE2 and SCORE2-OP without diabetes, the CKD Add-on (eGFR only) and CKD Add-on (eGFR + ACR) improved c-statistic by 0.006 (95% CI 0.005–0.008) and 0.018 (0.012–0.024), respectively, for SCORE2 and 0.012 (0.009–0.015) and 0.023 (0.013–0.032), respectively, for SCORE2-OP. Similar results were seen when we included individuals with diabetes and tested the CKD Add-on (eGFR + dipstick). In 57, 485 European participants with CKD, SCORE2 or SCORE2-OP with a CKD Add-on showed a significant NRI (e.g., 0.100 [0.062–0.138] for SCORE2) compared to the qualitative approach in the ESC guideline. Conclusion: Our Add-ons with CKD measures improved CVD risk prediction beyond SCORE2 and SCORE2-OP. This approach will help clinicians and patients with CKD refine risk prediction and further personalize preventive therapies for CVD. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): US National Kidney Foundation funding as well as US NIDDK